DEVELOPMENT OF COMMUNICATIVE COMPETENCE THROUGH THE AUDIO-LINGUAL METHOD - Xalimova, Lola; Yugay, Evgeniya Viktorovna (INTERNATIONAL CONFERENCE DEDICATED TO THE ROLE AND IMPORTANCE OF INNOVATIVE EDUCATION IN THE 21ST CENTURY, 2022)
Language as means for communication takes an important role in our daily activities. In this modern era, people are demanded to acquire more than one language. And this scientific article describes the Audio-Lingual method which aims to develop communicative competence of students through dialogues